The Recognition of The Factors Effective on The Shrinkage of Parts Polyamide 6 Through Using Design of Experiments Method - Noghondarian, Kazem; Sadraee, Mani (Asia Pacific Journal of Management and Education (APJME), 2019)
Paying more attention to quality, reduction of production waste, reduction of final cost of products and resisting in competitive market, fully clarifies the necessity for using the methods like “Design of Experiments”. In this Method in put variable of process are defined and to achieve the determined quality Principles, the effect on response variable are studied while performing changes through input variables systematically using statistical methods. In this article, Design of Experiments has been used for accessing the rate of standard shrinkage of Parts Polyamide 6 and also reducing the waste of the products which are made of Polyamide 6 in Fardan Electric Company.